Analisis Penerapan Kurikulum Merdeka pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMP Negeri 21 Kota Padang - Ahsan Nadya; Misra Misra (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This research examines the implementation of the Islamic Religious Education and Character Education curriculum at SMP Negeri 21 Padang City. The curriculum is a set of plans and arrangements regarding the learning system to achieve predetermined goals. In this research, qualitative methods were used to collect data with data analysis using a data triangulation approach. The conclusion is that SMP Negeri 21 Padang City has tried its best to implement the Islamic Religious Education and Character Education curriculum by referring to the independent curriculum. However, there are still several things that need to be considered in the form of objectives, content/materials, strategies/methods, and evaluation.